Implication Of Regional Tax Regulation On The Investment Climate And Its Reference To Omnibus Bill On Taxation - Debora Kristina Doloksaribu (Widya Yuridika, 2020)
AbstractThe granting of autonomy to the regions is intended to provide democratic space and public participation. Legal certainty in the administration of regional government specifically related to taxes is very crucial, especially for economic development, as it affects the investment climate. Any discrepancy between regional and central policies is seen as an obstacle in optimizing investment performance in the regions. The Government has proposed a Bill on General Provisions and Tax Facilities for Strengthening the Economy or also known as the Omnibus Bill on Taxation which regulates, among other things, regional tax and levy. The method used in this study is the type of legal research (normative) and carried out by examining library materials or secondary data in the form of various legal references, including primary, secondary, and tertiary materials. A descriptive technique is used in analyzing legal materials that have been collected. Writer opines that the Omnibus Bill is expected to provide business certainty, in the hope that it can increase investment. However, the discussion of the Omnibus Bill must be carefully done. There has to be a certainty and clarity of the intervention procedures of the central government so that it is carried out in a clear legal corridor.  AbstrakPemberian otonomi kepada daerah dimaksudkan untuk memberikan ruang demokrasi dan partisipasi masyarakat. Kepastian hukum dalam penyelenggaraan pemerintahan daerah merupakan hal yang sangat penting terutama dalam pembangunan di bidang ekonomi karena hal tersebut mempengaruhi iklim investasi. Adanya ketidaksinkronan kebijakan daerah dengan pusat dinilai sebagai hambatan dalam optimalisasi kinerja investasi di daerah. Pemerintah telah mengajukan Rancangan Undang-Undang Ketentuan Umum dan Fasilitas Perpajakan Untuk Penguatan Perekonomian atau RUU Omnibus Perpajakan yang salah satunya mengatur tentang pajak daerah dan retribusi daerah. Metode yang digunakan dalam penelitian ini adalah jenis penelitian hukum (normatif) dan dilakukan dengan menelaah bahan pustaka atau data sekunder berupa berbagai acuan hukum, baik bahan hukum primer, sekunder, maupun tersier. Teknik deskriptif digunakan dalam menganalisis bahan hukum yang telah dikumpulkan. Penulis berpendapat bahwa Omnibus Law Perpajakan dapat memberikan kepastian berusaha sehingga investasi semakin meningkat. Namun demikian, pembahasan RUU Omnibus Law harus dilakukan dengan cermat dan hati-hati. Harus ada kepastian dan kejelasan prosedur intervensi dari pemerintah pusat sehingga pelaksanaannya berada dalam koridor hukum yang jelas.